Impact of electric vehicles on low‐voltage residential distribution networks: A probabilistic analysis - Matthias Hungbo; Mingchen Gu; Lasantha Meegahapola; Timothy Littler; Siqi Bu (IET Smart Grid, 2023)
Abstract The past two decades have seen a rapid increase in electric vehicles (EVs) for several reasons, such as policy directives to reduce carbon emissions in the transport sector and technology advancements in the EV industry. However, this has increased the load demand on the power grid, especially in the low‐voltage (LV) network, as most EVs are charged at EV owner premises. This paper investigates the impact of EVs on the LV residential distribution network using a probabilistic modelling framework. Probability distribution functions for EV charging power are derived using the United Kingdom (UK) EV dataset. The study has investigated multiple EV penetration levels, different probability distribution functions for EV charging representation, vehicle‐to‐grid (V2G), solar photovoltaic (PV) generation, and the volt‐var capability of the solar‐PV inverter. The results have shown that as EV penetration increases in the distribution network, there is a significant increase in transformer loading and a decrease in the steady‐state voltage levels. V2G has positively impacted the distribution network. A case study carried out on a real LV feeder with solar‐PV generation has shown how PV generation and volt‐var functionality of the PV inverter help reduce the impact of EV charging and V2G.